The Influence of Domestic Politics of South Korea on its Relations with North Korea and the United States - Miftah Farid Darussalam (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This paper aims to conduct research on the influence of domestic South Korean politics on relations with the United States and North Korea. In this case, the theory of dominance of domestic political actors explains where the dominance of a group will have an influence on determining the foreign policy of a country. South Korea’s domestic politics is dominated by two groups with different ideologies in the face of the United States and North Korea. This then resulted in different actions in the face of North Korea and the United States. The differences will be explained by assessing some of the policies applied to Kim Dae Jung’s regime and Roh Moo-Hyun from a progressive group. The policy will then be compared to the policies of the regime of Lee Myung Bak from conservative groups. Differences in the group’s dominant views in South Korea have led to certain strategies for each group in the face of the opposition group. The strategy is carried out to maintain the effectiveness of the policies applied according to the ideology of each group. This research used literature study as the method by taking data from journals and reports which that discuss the national politics of South Korea. The theoretical framework of V.M Hudson, which focuses on the national circumstances, and the role of domestic actors have been applied in this research.